2021
DOI: 10.1108/jes-07-2020-0317
|View full text |Cite
|
Sign up to set email alerts
|

Does financial inclusion induce poverty, income inequality, and financial stability: empirical evidence from the 54 African countries?

Abstract: PurposeThe aim of the study is to examine the impact of financial inclusion on poverty, income inequality and financial stability using panel data of 54 African countries.Design/methodology/approachTo achieve this objective, the current study used multiple regressions across an unbalanced panel data of 54 African countries which are based on the four years mean value for the period 2001–2019.FindingsThe results show that financial inclusion (FI) is a valuable indicator; it reduces poverty, income inequality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 45 publications
7
43
0
1
Order By: Relevance
“…The relationship between inclusive finance and disposable income has unique implications for low-income households, but previous research has largely ignored these issues. Previous research on financial inclusion was mainly conceptual, and empirical research based on publicly available data is scarce (Khan et al, 2022). Some of those studies seem worthwhile and deserving of investigation with regard to low-income households.…”
Section: The Originality Of the Studymentioning
confidence: 99%
“…The relationship between inclusive finance and disposable income has unique implications for low-income households, but previous research has largely ignored these issues. Previous research on financial inclusion was mainly conceptual, and empirical research based on publicly available data is scarce (Khan et al, 2022). Some of those studies seem worthwhile and deserving of investigation with regard to low-income households.…”
Section: The Originality Of the Studymentioning
confidence: 99%
“…The second aspect is the poverty alleviation effect and mechanism. E-commerce facilitates rural industrial development by promoting information sharing, factor flow, and resource docking [17], and has an obvious positive effect on the increase in the income of enterprises in poverty-stricken areas [18]; this is the "endogenous driving force" to promote economic development in impoverished areas [19]. At the same time, e-commerce has effectively alleviated the problem of low-price sales caused by slow sales and information asymmetry.…”
Section: Research On E-commerce Poverty Alleviationmentioning
confidence: 99%
“…They also found a positive and significant impact of financial inclusion on economic growth. The most recent, Khan et al (2021) examined, using panel data, the impact of financial inclusion on poverty, income inequality and financial stability between 2001-2019 for 54 African countries. They suggested that, financial inclusion reduces poverty, income inequality and improves financial stability.…”
Section: Country Level Studies In African Regionmentioning
confidence: 99%